2019
DOI: 10.1021/acssynbio.9b00224
|View full text |Cite
|
Sign up to set email alerts
|

CReasPy-Cloning: A Method for Simultaneous Cloning and Engineering of Megabase-Sized Genomes in Yeast Using the CRISPR-Cas9 System

Abstract: Over the past decade, a new strategy was developed to bypass the difficulties to genetically engineer some microbial species by transferring (or "cloning") their genome into another organism that is amenable to efficient genetic modifications and therefore acts as a living workbench. As such, the yeast Saccharomyces cerevisiae has been used to clone and engineer genomes from viruses, bacteria, and algae. The cloning step requires the insertion of yeast genetic elements in the genome of interest, in order to dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…Our previous study in engineered Escherichia coli showed that the common error mode was disruption by mobile elements. , These results imply that one should consider a common error mode of engineered microbes to find an optimal biosensor design. Strong recombination activity in yeast can be applied for various purposes but can also cause instability in the engineered strain . We expect that deleting the potential homology region ( GFA1 locus on the genome in our case) will further improve the production stability; therefore, understanding the common error mode will be critical to operating long-term cultivation with engineered hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study in engineered Escherichia coli showed that the common error mode was disruption by mobile elements. , These results imply that one should consider a common error mode of engineered microbes to find an optimal biosensor design. Strong recombination activity in yeast can be applied for various purposes but can also cause instability in the engineered strain . We expect that deleting the potential homology region ( GFA1 locus on the genome in our case) will further improve the production stability; therefore, understanding the common error mode will be critical to operating long-term cultivation with engineered hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, the genome of M. pneumoniae has also been cloned as a yeast centromeric plasmid and successfully edited using the CreasPy-cloning technique. 35 In spite of this, the reintroduction of this in-yeast engineered M. pneumoniae genome into a Mycoplasma acceptor cell (i.e., genome transplantation) has never been reported. Therefore, although the M. pneumoniae genome can be edited in yeast, the generation of M. pneumoniae edited cells remains unsolved.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Alternatively, a more affordable strategy is to clone naturally existing Mycoplasma genomes as yeast circular centromeric plasmids . These genomes can later be comprehensively modified using the state-of-the-art editing tools available for yeast before their reintroduction into a recipient Mycoplasma cell (i.e., genome transplantation) . This complete cycle of cloning, in-yeast modification, and genome transplantation, has led to the generation of a fully attenuated M. mycoides subsp.…”
mentioning
confidence: 99%
“…Alternatively, once the genome is cloned in yeast, the plasmid backbone can be moved to a different location by co-transformation of a plasmid containing homology hooks to the new location and another fragment that will delete the plasmid in the original location and restore the interrupted gene. Finally, a CRISPR/Cas9 system can be devised to produce appropriate cut-sites at the desired location [39,40]. The linearized algal mitochondria genome was captured by transforming it into S. cerevisiae along with a PCR-amplified plasmid backbone containing homology on each end to the organellar regions flanking the cut-site.…”
Section: Design-build-test Cycle To Enable Rapid Engineering Of Organelle Genomesmentioning
confidence: 99%